Age Differences in Daily and Nondaily Cannabis Use in the United States, 2002–2014 - Mauro, Pia M. (J Stud Alcohol Drugs, 2018)
OBJECTIVE: Adult cannabis use has increased in the United States since 2002, particularly after 2007, contrasting with stable/declining trends among youth. We investigated whether specific age groups disproportionately contributed to changes in daily and nondaily cannabis use trends. METHOD: Participants ages 12 and older (N = 722,653) from the 2002–2014 National Survey on Drug Use and Health reported past-year cannabis use frequency (i.e., daily = ≥300 days/year; nondaily = 1–299 days/year; none). Multinomial logistic regression was used to model change in past-year daily and nondaily cannabis use prevalence by age group (i.e., 12–17, 18–25, 26–34, 35–49, 50–64, ≥65), before and after 2007. Multinomial logistic regressions estimated change in relative odds of cannabis use frequency over time by age, adjusting for other sociodemographics. RESULTS: Daily cannabis use prevalence decreased in ages 12–17 before 2007 and increased significantly across adult age categories only after 2007. Increases did not differ significantly across adult ages 18–64 and ranged between 1 and 2 percentage points. Nondaily cannabis use decreased among respondents ages 12–25 and 35–49 before 2007 and increased across adult age categories after 2007, particularly among adults 26–34 (i.e., 4.5 percentage points). Adjusted odds of daily versus nondaily cannabis use increased after 2007 for ages 12–64. CONCLUSIONS: Increases in daily and nondaily cannabis use prevalence after 2007 were specific to adult age groups in the context of increasingly permissive cannabis legislation, attitudes, and lower risk perception. Although any cannabis use may be decreasing among teens, relative odds of more frequent use among users increased in ages 12–64 since 2007. Studies should assess not only any cannabis use, but also frequency of use, to target prevention efforts of adverse effects of cannabis that are especially likely among frequent users.